Effect of Applying Mandatory Governance Rules to Risk Management - Rashwan, Abd El Rahman; Kassem, Zainab (The Arab Journal of Administration, 2020)
The main aim of the research is to establish scientific foundations by identifying the impact of the application of mandatory governance rules on risk management in the investment sector companies listed on the Palestine Exchange. To answer the research questions and test the hypotheses of the research, the researcher relied on the analytical descriptive method in explaining and clarifying the theoretical side, and analyzing the results of the applied study. The results of the research also showed that there is an effective control system in the companies of the investment sector listed on the Palestine Exchange, which is closely related to risk management and is an essential aspect of corporate governance. The study also recommended that the companies of the investment sector listed on the Palestine Exchange establish a comprehensive framework for risk management in each department and management within these companies.